Effects of Low-Intensity Pulsed Ultrasound on Knee Osteoarthritis: A Meta-Analysis of Randomized Clinical Trials. (15th July 2018) - Zhou, Xiao-Yi; Zhang, Xiao-Xi; Yu, Guan-Yu; Zhang, Zi-Cheng; Wang, Fei; Yang, Yi-Lin; Li, Ming; Wei, Xian-Zhao
Abstract : Background . Osteoarthritis (OA) is a common degeneration disease characterized with joint pain. The aim of the present study was to systemically review the effects of LIPUS on pain relief and functional recovery in patients with knee osteoarthritis (OA). Methods . PubMed, Embase, and Cochrane Library were searched manually for researches on LIPUS treatment in patients with knee OA from 1945 to July 2017. Two investigators independently selected the studies according to the inclusion and exclusion criteria, extracted the concerned data, and assessed the included studies. Meta-analysis was performed to evaluate VAS, WOMAC, and ambulation speed between control and LIPUS groups. Results . Five studies were selected in this study. Compared with control group, LIPUS group received a decrease of pain intensity with moderate heterogeneity (-0.79, 95% CI, -1.57 to 0.00; I 2 = 65%, P = 0.04) by VAS and improvement in knee function by WOMAC (-5.30, 95% CI, -2.88 to -7.71; I 2 = 44%, P = 0.17). No significant improvement was found in ambulation speed (0.08 m/s, 95% CI, -0.02 to 0.18 m/s; I 2 = 68%, P = 0.03). Conclusion . The present study includes 5 high quality randomized controlled trials. The result indicated that LIPUS, used to treat knee OA without any adverse effect, had a beneficial effect on pain relief and knee functional recovery. More evidence is needed to prove whether LIPUS is effective in improving walking ability.